Long-Term Outcomes of Microsurgical Nasal Replantation: Review of the Literature and Illustrated 10-Year Follow-Up of a Pediatric Case with Full Sensory Recovery - Marsden, Nicholas J.; Kyle, Amanda; Jessop, Zita M.; Whitaker, Iain S.; Laing, Hamish (Frontiers in Surgery, 2015)
We present a case of successful artery only total nose replantation in an 18 month-old child, with 10 years of follow up and full sensory recovery despite no nerve repair. The common absence of veins for anastomosis does not prevent successful replant, as demonstrated with the use of Hirudin medicinalis use in this unique case. We comprehensively review the literature of this rare and complex injury and advocate microsurgical replantation where possible over other methods of nasal reconstruction.